The institution of instigating and reopening discontinued preparatory proceedings as a method to terminate proceedings because of detection activities undertaken by the Police X Archives - Kurowski, Michał (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
The institutions of reopening and instituting discontinued preparatory proceedings are of the key importance as regards a possibility of returning to criminal proceedings already finished. Principles of criminal proceedings deciding how to conduct them in certain circumstances force completion of the proceedings at a given stage. Sometimes this is due to the appearance of a relative, therefore removable, negative procedural condition, sometimes due to the impossibility of detecting perpetrators of the offence. It is therefore crucial to establish what conditions to return to the discontinued preparatory proceedings are. Is it possible? What is the time frame for a decision to be made? This study provides answers to the problems identified, focusing obviously on the procedural conditions of admissibility of the return to criminal proceedings. The rules have been laid down in the law system according to the time of proceedings completion. The article also presents such elements as bodies authorised to act, conditions of the prosecutor’s operations, a role and a place of the Police in the decision-making system. The mentioned elements are an attempt to locate these particular institutions in the system of revealing some old crimes committed by perpetrators not yet disclosed.